2013
DOI: 10.25336/p65c9r
|View full text |Cite
|
Sign up to set email alerts
|

Survival advantage of siblings and spouses of centenarians in 20th-century Quebec

Abstract: Longevity runs in families, either through genetic or environmental influences. Using Quebec civil registration and historical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 44 publications
(45 reference statements)
3
20
0
Order By: Relevance
“…The within-family study demonstrated that being born to a younger mother increases the chances of becoming a centenarian, which is consistent with our previous study on another sample of centenarians (Gavrilov and Gavrilova 2012) as well as the study of Canadian centenarians (Jarry et al 2012b). Being born in the second half of the year is beneficial for longevity as shown by both the within-family (Gavrilov and Gavrilova 2011) and the between-family analyses presented in this paper.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The within-family study demonstrated that being born to a younger mother increases the chances of becoming a centenarian, which is consistent with our previous study on another sample of centenarians (Gavrilov and Gavrilova 2012) as well as the study of Canadian centenarians (Jarry et al 2012b). Being born in the second half of the year is beneficial for longevity as shown by both the within-family (Gavrilov and Gavrilova 2011) and the between-family analyses presented in this paper.…”
Section: Discussionsupporting
confidence: 91%
“…The within-family analysis of the paternal- and maternal-age effects on human longevity demonstrated that a young age of the mother increases the chances of children to reach longevity (see also Gavrilov and Gavrilova 2012; Gavrilova and Gavrilov 2007; Jarry et al 2012b; Myrskylä et al 2013). The finding of a beneficial effect of young maternal age on offspring survival to age 100 in humans is similarly also reported for laboratory animals (Carnes et al 2012; Tarin et al 2005), and hence may have a biological explanation.…”
Section: Centenarians Compared To Their Shorter-lived Siblings: Thementioning
confidence: 99%
“…The importance of family in contributing to health and longevity is well-recognised. Many studies have shown that parents and siblings of centenarians have a survival advantage compared to other members of their birth cohort (Perls et al 1998(Perls et al , 2002Willcox et al 2006;Jarry et al 2012). Yet, of several siblings in a centenarian family, often only one will live to or beyond the age of 100 years.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that spouses (F2) who married longevous IPs (F2) did not live significantly longer than spouses (F2) who married a non-longevous IP (F2) in the UPDB while they did in LINKS. Literature is inconclusive about the potential survival advantage of spouses of long-lived persons 5,6,8,39,40 . Pedersen et al (2017) observed a survival advantage in the Long Life Family Study for spouses of long-lived siblings when comparing them to a birth cohort and sex matched control group.…”
Section: Discussionmentioning
confidence: 99%
“…The authors point to assortative mating as a factor explaining the survival advantage for these spouses 5 . A Quebec study, focused on the spouses of 806 centenarians, also reported a survival advantage 39 and a study of Southern Italy demonstrated that male nonagenarians outlived their spouses, whereas this was not the case for female nonagenarians 40 . A recent study showed that the spouses of 944 nonagenarians had no survival advantage but a life-long sustained survival pattern similar to the general population 8 .…”
Section: Discussionmentioning
confidence: 99%